Cut the red tape for R&D funding - Abd Razak, Dzulkifli (2007)
TODAY is the last day for local universities to showcase their inventions and innovations. Under the new brand, "Pecipta", an acronym for International Conference and Exposition of Inventions in Institutions of Higher Learning, it aims to bridge the perceived gap between universities and the industry and community. This could be an avenue for the discoveries to be adopted for commercialisation by the local industry. Despite being commonly misunderstood, some of these discoveries took years to develop and are backed by numerous publications in internationally accepted journals. Research and development is an essential component in bringing about novel inventions worthy of heightening the quality of life. Neglecting R&D or having a poorly structured system, the aspirations of the government in spearheading national development driven by R&D will be defeated.